MENGINTEGRASIKAN SEJARAH MATEMATIKA DAN PENDEKATAN GEOMETRIS DALAM PEMAHAMAN PERSAMAAN KUADRAT - Widyastuti, Eri; Wardahlia, Firli; Sinaga, Irene Yoseva; Khazanah, Khazanah; br Jawak, Lady Christine Elizabeth; Sirait, Nazla Annisa Gunawan; Tampubolon, Polin Jeremia (Universitas Islam Sumatera Utara, 2024)
This study explores the integration of the history of mathematics and geometric approaches in enhancing students' understanding of quadratic equations. The research indicates that students who engage in this learning process can establish connections between geometric manipulations and algebraic symbols used in quadratic equations. By converting geometric forms into algebraic expressions and vice versa, students gain a deeper understanding of concepts such as factorization and perfect square solutions. The integration of historical mathematics and geometric approaches proves to be effective in improving students' conceptual understanding and overcoming learning barriers. Visualizations, particularly through methods Geometry, allow students to build a more intuitive understanding of quadratic equations, thereby increasing their interest and motivation in learning